Schauder Fixed Point Theorems in Intuitionistic Fuzzy Metric Space - Kadhm, Amani E. (Iraqi Journal of Science, 2022)
In this paper, we will study a concepts of sectional intuitionistic fuzzy continuous and prove the schauder fixed point theorem in intuitionistic fuzzy metric space as a generalization of fuzzy metric space and prove a nother version of schauder fixed point theorem in intuitionistic fuzzy metric space as a generalization to the other types of fixed point theorems in intuitionistic fuzzy metric space considered by other researchers, as well as, to the usual intuitionistic fuzzy metric space.